Implementation of the Community Police Program in Supporting the Maintenance of Security and Public Order (Study at the Semarang City Police Resort) - Maulidiawati, Wahdah; Laksana, Andri Winjaya (Jurnal Hukum Khaira Ummah, 2025)
Abstract. The current conducive Kamtibmas situation is highly expected by the entire community to be realized in the midst of society so as to create a sense of calm and peace, therefore an intensive approach to the community is very necessary. The purpose of this study is to determine and analyze the implementation of the neighborhood police program in supporting the maintenance of public security and order. To determine and analyze the factors that hinder the implementation of the neighborhood police program in supporting the maintenance of public security and order and their solutions. The method used by the researcher is a legal approach in a sociological juridical manner and the specifications in this study are descriptive analytical. The sources and types of data in this study are primary data obtained through interviews and secondary data obtained from literature studies. The data is analyzed qualitatively using criminal law policy theory and legal system theory. Based on the results of the study, the implementation of the Community Police (RW Police) program in supporting the maintenance of public security and order (Kamtibmas) aims to create a closer relationship between the police and the community at the smallest level, namely RW, has been implemented well although not optimally. Factors that hinder the implementation of the community police program in supporting the maintenance of public security and order include the placement of Human Resources, namely not all RW Police Officers can be placed where they live, the budget, namely the absence of a special budget for RW Police Officers, both operational budgets and contact facilities, and the performance of the RW Police which is not optimal due to the burden of the RW Police members who also have to carry out their daily operational duties. The solution that can be done is careful planning regarding the placement of RW Police officers and renewing the duty order, so that the RW Police should be placed according to their place of residence. If in an RW there are no residents who work as members of the Police, then it is better for Polri members to serve in an office that is not far from the RW, thus it is hoped that the assignment of the RW Police can support the task of maintaining harkamtibmas optimally. Proposed budget to support RW Police activities, such as operational facilities and contact facilities and other supporting facilities. So that Polri members assigned as RW Police do not often get field operational tasks or other additional tasks.